1998
DOI: 10.1002/(sici)1099-0720(199812)12:7<s77::aid-acp601>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, dissociation, and fantasy-proneness as predictors of memory distortion in autobiographical and laboratory-generated memories

Abstract: Individual differences in susceptibility to memory distortion in autobiographical and laboratory‐generated memories were examined. Subjects from an earlier autobiographical memory study completed three personality measures and a list learning task designed to elicit false memories. Scores on the Tellegen Absorption Scale were negatively correlated with accuracy of the autobiographical memory. None of the personality measures predicted the occurrence of false memories in the laboratory task. Distortion of autob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 17 publications
4
72
1
Order By: Relevance
“…The critical dierence between these studies might be the absence or presence of suggestive techniques to induce memory distortions. That is, the connection between DES and interrogative suggestibility found in our study seems to indicate that studies using suggestive maneuvers to induce pseudomemories will be more successful in detecting a connection between DES and autobiographical memory distortion than studies examining the more or less spontaneous memory distortions that develop over time (Platt et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The critical dierence between these studies might be the absence or presence of suggestive techniques to induce memory distortions. That is, the connection between DES and interrogative suggestibility found in our study seems to indicate that studies using suggestive maneuvers to induce pseudomemories will be more successful in detecting a connection between DES and autobiographical memory distortion than studies examining the more or less spontaneous memory distortions that develop over time (Platt et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, evidence was found to support the notion that self-reported cognitive eciency plays a mediating role in the link between DES and suggestibility. The current results may help explain why some studies found the DES to be a powerful predictor of autobiographical memory distortion (e.g., Hyman & Billings, 1998), while other studies failed to replicate this phenomenon (e.g., Platt, Lacey, Iobst, & Finkelman, 1998). The critical dierence between these studies might be the absence or presence of suggestive techniques to induce memory distortions.…”
Section: Discussionmentioning
confidence: 91%
“…The m easure of fantasy proneness in this study w as the Inventory of Childhood Memories and Imaginings, a m easure of involvement in fantasy both as a child and as an adult that was also used to construct the CEQ [27]. The authors speculate that those who score high on absorption are more inclined to incorporate post-event information of any sort into the memory reconstruction process [30].…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, research relying on the ICMI as an index of fantasy proneness reported correlations with TAS of a similar magnitude (e.g. r=0.77; Platt, Lacey, Iobst & Finkelman, 1998).…”
Section: Correlatesmentioning
confidence: 99%